The Causes Of The High Level Of Plagiarism In The Preparation Of Scientific Work In Islamic Education - Aminah, Aminah (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2023)
This study aimed to identify the causes of the high level of plagiarism in the preparation of scientific papers of Postgraduate Islamic Education students of Pontianak State Islamic Institute. The results of this research can be used as a reference solution to overcome the problem of plagiarism of scientific work in Islamic Education. A qualitative approach with phenomenology type was used in this research. The subjects of this research are the data collected are papers or other written works made during the Strata-2 (S-2) course consisting of, (1) students of the Islamic Education study program of IAIN Pontianak Postgraduate Class XV totaling 4 people, (2) lecturers of the Islamic Education study program of IAIN Pontianak Postgraduate Class XV totaling 4 people, and (3) leaders of the Islamic Education study program of IAIN Pontianak Postgraduate Class XV totaling 2 people. Data collection techniques and instruments used were, (1) interview techniques with semi-structured interview guideline instruments and (2) documentation studies with instruments in the form of documents and photographs. Data analysis was conducted using the Strauss and Corbin model. The results of this study found 5 (five) causes of plagiarism behavior that occurred in assignments in the form of scientific papers, namely, (1) difficulty finding references in writing scientific papers, (2) difficulty processing reading material from references, (3) there is no guidebook for writing scientific papers, (4) leniency in monitoring plagiarism behavior, and (5) less strict sanctions for plagiarism behavior.